2010
DOI: 10.4196/kjpp.2010.14.6.391
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Induces Downregulation of E2F4 Expression and Apoptotic Cell Death in HCT116 Human Colon Cancer Cells; Involvement of Reactive Oxygen Species

Abstract: E2F transcription factors and their target genes have been known to play an important role in cell growth control. W e found that curcumin, a polyphenolic phytochemical isolated from the plant Curcuma longa, markedly suppressed E2F4 expression in HCT116 colon cancer cells. Hydrogen peroxide was also found to decrease E2F4 protein level, indicating the involvement of reactive oxygen species (ROS) in curucmin-induced downregulation of E2F4 expression. Involvement of ROS in E2F4 downregulation in response to curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…The mechanisms underlying the inhibition of E2F4 and cyclin expression under MI deficiency are unknown but might be partially related to the increase in ROS. As mentioned above, ROS are involved in the down-regulation of E2F4 expression and the inhibition of the proliferation of HCT116 human colon cancer cells [35]. In the present study, we observed that MI deficiency caused an induction of ROS production in both the head kidney and spleen, which supported our hypothesis.…”
Section: Deficiency Caused Oxidative Damage and Disturbed The Antisupporting
confidence: 90%
See 1 more Smart Citation
“…The mechanisms underlying the inhibition of E2F4 and cyclin expression under MI deficiency are unknown but might be partially related to the increase in ROS. As mentioned above, ROS are involved in the down-regulation of E2F4 expression and the inhibition of the proliferation of HCT116 human colon cancer cells [35]. In the present study, we observed that MI deficiency caused an induction of ROS production in both the head kidney and spleen, which supported our hypothesis.…”
Section: Deficiency Caused Oxidative Damage and Disturbed The Antisupporting
confidence: 90%
“…Furthermore, our previous study demonstrated that MI deficiency caused a decrease in the ROS scavenging ability in the intestines of juvenile Jian carp [6]. Kim and Lee reported that ROS are involved in down-regulation of E2F4 expression and the inhibition of the proliferation of HCT116 human colon cancer cells [35]. Recently, our laboratory cloned cyclin D, cyclin E and E2F4 from Jian carp; cyclin A was previously cloned by Liu et al (Genebank access No.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several mechanisms to explain the antioxidant, antiinflammatory and anticancer effect of curcumin [25][26][27][28][29]. Autophagy which is designated as type II programmed cell death has also been reported to be an anticancer mechanism of curumin, resulting in the growth inhibition of a variety of malignant of cells such as chronic myeloid leukemia cells, malignant glioma cells, and oesophageal cancer cells [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…GSH plays a central role in maintaining redox homeostasis [4]. Elevated ROS elicit a variety of oxidative stress responses ranging from cell proliferation to growth arrest to cell death [5,6]. The particular outcome can vary depending on cell type as well as the concentration and duration of ROS exposure.…”
Section: Introductionmentioning
confidence: 99%